Optimizing the Quran Memorization Program Using the Jibril Method in Elementary Madrasah - Uswatun Hasanah; Muhammad Fadhlan Refa (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to analyze the implementation of the Jibril method in the Qur’anic memorization (tahfidz) program for sixth-grade students at MI Darussalam Badang Ngoro Jombang. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the headmaster, tahfidz teachers, and students participating in the memorization program. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the implementation of the Jibril method in Qur’anic memorization learning is carried out through systematic learning stages, including muraja’ah (review of previous memorization), teacher recitation as a model (talqin), students’ imitation of the recitation (ittiba’), independent memorization, and individual memorization submission to the teacher as an evaluation process. The application of the Jibril method helps students understand the correct pronunciation of Qur’anic verses before memorizing them, thereby improving both the accuracy of recitation and the quality of memorization. In addition, routine muraja’ah activities and continuous evaluation play a significant role in maintaining students’ memorization. This study suggests that the Jibril method can serve as an effective strategy for improving Qur’anic reading and memorization skills among Islamic elementary school students.